Management of the patient at high risk for breast cancer - Hansen, Nora M. (Springer)
Management of the Patient at High Risk for Breast Cancer provides a state-of-the art review of patients who are at high risk for breast cancer, how to identify them, the tools available for risk assessment and quantification and indications for genetic counseling and testing. The book summarizes the high risk breast imaging options, including newest techniques and schedules. Pathologic evaluation of high risk lesions are featured as well as the management issues surrounding these lesions. The volume also covers the management of concomitant cancer risk and screening strategies. A concise, yet comprehensive overview of the current status of the topic, Management of the Patient at High Risk for Breast Cancer serves as a useful resource for physicians and researchers dealing with and interested in patients at high risk for breast cancer. Identifying women at high risk of breast cancer: understanding the risk models - Genetic and genomic factors in breast cancer - Brca mutation - High risk breast lesions and pathologic evaluation - Management of high risk lesions - Radiologic imaging for the high risk patient - Risk reduction strategies: medical oncology - Risk reduction strategies: surgical perspective - Options and advances in breast reconstruction - Management of concomitant cancer risk - Psychological implications of testing positive for the brca gene - The high tech high risk clinic - Current and future direction in basic and translational research.